PENGGUNAAN MEDIA ALTERNATIF (WHATSAPP) SELAMA PANDEMI COVID-19 DI SEKOLAH DASAR - Ageng Riasty; Arum Ndalu; Adilla Salsa Afifah Amalia; Arief Cahyo Utomo (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The Covid-19 pandemic is increasing drastically every day. Its impact has made all aspects of people's lives change. One of them is in education. Therefore, the government implements distance or online learning, where children start learning from their respective homes without the need to go to school. In this case, schools, especially teachers, are required to try to create learning to keep it going even though they are not in direct school and choose the use of media or platforms used for online learning that are easy to use by students. This research uses descriptive qualitative methods, by collecting data through observation, interviews and documentation conducted at SD Negeri 15 Sragen. Researchers found that during online learning the teacher chose to use the platform WhatsApp. Students assess online learning using alternative media WhatsApp is very popular with students compared to using learning media or other platforms. Through the WhatsApp application the teacher can provide material in writing, orally, send videos, send YouTube links, and also teachers can make video calls when there are students who have difficulty understanding the lesson.